2020
DOI: 10.1002/dac.4511
|View full text |Cite
|
Sign up to set email alerts
|

A lightweight anonymous two‐factor authentication protocol for wireless sensor networks in Internet of Vehicles

Abstract: SummaryInternet of Vehicles (IoV), as the next generation of transportation systems, tries to make highway and public transportation more secure than used to be. In this system, users use public channels for their communication so they can be the victims of passive or active attacks. Therefore, a secure authentication protocol is essential for IoV; consequently, many protocols are presented to provide secure authentication for IoV. In 2018, Yu et al proposed a secure authentication protocol for WSNs in vehicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…en, Yu et al [25] proposed an authenticated protocol in vehicular communications. In 2020, Sadri et al [26] demonstrated that Yu et al's protocol [25] was susceptible to sensor capture attacks and impersonation attacks and could not provide traceability. Additionally, Sadri and Rajabzadeh Asaar [26] proposed a protocol in the IoV environment, which was based on lightweight primitives.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…en, Yu et al [25] proposed an authenticated protocol in vehicular communications. In 2020, Sadri et al [26] demonstrated that Yu et al's protocol [25] was susceptible to sensor capture attacks and impersonation attacks and could not provide traceability. Additionally, Sadri and Rajabzadeh Asaar [26] proposed a protocol in the IoV environment, which was based on lightweight primitives.…”
Section: Related Workmentioning
confidence: 99%
“…In 2020, Sadri et al [26] demonstrated that Yu et al's protocol [25] was susceptible to sensor capture attacks and impersonation attacks and could not provide traceability. Additionally, Sadri and Rajabzadeh Asaar [26] proposed a protocol in the IoV environment, which was based on lightweight primitives. In 2021, Wu et al [27] proposed a protocol in IoV, and the protocol realized authentication key exchange (AKE).…”
Section: Related Workmentioning
confidence: 99%
“…en Yu et al proposed a new security authentication protocol and proved that their protocol can resist various known attacks. In 2020, Sadri and Rajabzadeh Asaar [41] proved that Yu et al's protocol is vulnerable to tracking attacks, impersonation attacks, sensor capture attacks, and so forth and proposed a secure protocol for application in VANETs.…”
Section: Related Workmentioning
confidence: 99%
“…This means that the user's identity is disclosed only to an authorized set of GWN and IoT sensing devices during the authentication sessions. Therefore, to preserve user privacy, authenticated key agreement schemes [23][24][25][26][27] thwart attempts to disclose or link users' identities by exploiting their authentication sessions.…”
Section: Related Workmentioning
confidence: 99%